1989
DOI: 10.1259/0007-1285-62-737-443
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic correction of vesico-ureteric reflux by subureteric Teflon injection: follow-up ultrasound and voiding cystography

Abstract: The technique of subureteric Teflon injection for the correction of vesico-ureteric reflux was first described by Puri and O'Donnell in 1984. The Teflon granuloma that occurs after the injection anchors the submucosal ureter, thereby preventing reflux. This paper reviews the ultrasound and cystographic findings in 88 patients with 115 refluxing ureters followed-up for periods ranging from 3 months to 3 years. Reflux disappeared in 91 ureters (79.1%) and the degree of reflux improved in 22 ureters (19.1%). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
2
11
0
1
Order By: Relevance
“…The number of new renal scars was higher in the deposit (−) group, meaning that the lack of the deposit might have influenced the condition of the kidney. Previous reports and our results all support the notion that successful anti-reflux treatment probably does influence the progression of reflux nephropathy in most cases [16,17]. The new information on STING treatment gained from our study (that the recurrence of reflux is significantly influenced by the absence of the Teflon deposit in the long-term) might be useful for those experts-paediatricians, paediatric nephrologists, urologists, paediatric surgeons and radiologists-who take part in the follow-up of children that have undergone subureteric Teflon injection.…”
Section: Discussionsupporting
confidence: 89%
“…The number of new renal scars was higher in the deposit (−) group, meaning that the lack of the deposit might have influenced the condition of the kidney. Previous reports and our results all support the notion that successful anti-reflux treatment probably does influence the progression of reflux nephropathy in most cases [16,17]. The new information on STING treatment gained from our study (that the recurrence of reflux is significantly influenced by the absence of the Teflon deposit in the long-term) might be useful for those experts-paediatricians, paediatric nephrologists, urologists, paediatric surgeons and radiologists-who take part in the follow-up of children that have undergone subureteric Teflon injection.…”
Section: Discussionsupporting
confidence: 89%
“…Of these, seven studies did not discuss the safety or tolerability of the treatment [11,13,33,35,36,44,45,50]. Among those six studies that did report some information on safety findings, the following was noted.…”
Section: Safety Of Endoscopic Injection In Duplex Systemsmentioning
confidence: 99%
“…[3][4][5][6] Being a noninvasive and widespread imaging modality, renal/bladder sonography has been widely used to determine the size and precise location of the subureteral mass as well as for the evaluation of hydroureteronephrosis after the injection. 3,5,[7][8][9][10] Although some investigators have suggested that the size and volume of the implant as assessed with imaging studies may be an important factor in predicting the outcome of the procedure, this assumption could not be supported entirely. 3,7,8 Recently, Herz et al 9 reported that sonography was accurate in identifying the presence of subureteral implant and correlating implant stability on renal sonography with correction of reflux after polydimethylsiloxane injection.…”
mentioning
confidence: 99%
“…3,5,[7][8][9][10] Although some investigators have suggested that the size and volume of the implant as assessed with imaging studies may be an important factor in predicting the outcome of the procedure, this assumption could not be supported entirely. 3,7,8 Recently, Herz et al 9 reported that sonography was accurate in identifying the presence of subureteral implant and correlating implant stability on renal sonography with correction of reflux after polydimethylsiloxane injection. In the current study, we describe the sonographic assessment of a subureteral implant after endoscopic DHA injection.…”
mentioning
confidence: 99%